BIOIMPEDANCE MARKERS AND TUBERCULOSIS OUTCOME AMONG HIV-INFECTED PATIENTS - Montalvo, Raúl; Bernabe-Ortiz, Antonio; Kirwan, Daniela E.; Gilman, Robert H. (African Journal of Infectious Diseases (AJID), 2018)
Background: The changes in body composition markers (weight, fat mass, lean mass, and BMI) over time can beassociated with TB treatment outcome among HIV-infected patients. The aim of this study was to investigate whetherchanges in fat mass and lean mass were associated with the treatment response among patients with HIV infection andpulmonary tuberculosis.Materials and Methods: This was a prospective cohort study. Data from HIV-infected patients commencing TBtherapy were analyzed. This included body weight measurement using bioimpedance equipment at baseline, onemonth, and two months after starting TB treatment.Results: The study was conducted in 125 patients, 17 patients (13.6%) died during treatment, of which 5 died duringthe first month of treatment, 4 during the second month and 8 after the second month. The group of patients with goodresponse, increased their weight by 1.3 kg (p <0.001) at the end of the first month of TB treatment and 2.6 kg in thesecond month (p <0.001), and body fat increase was 1.2 Kg (p <0.001) and 2.3 kg (p <0.001), the first and secondmonth respectively. The group of patients who died had lost 2.1 kg fat mass after the first month (p <0.001) and 3.7 kgin the second month (p <0.001).Conclusions: Our results show that the weight change during TB treatment (increased fat mass) helps us predicttherapeutic response. Weight loss during the first month of starting therapy should be evaluated thoroughly to identifythe probable cause of treatment failure.